To catch a cheat - Johnson, Varian (Arthur A. Levine Books, an imprint of Scholastic Inc., 2016)
Because of his reputation for practical jokes Jackson Greene is the automatic suspect for anything that goes wrong at school--but when he and his friends are framed for a crime they did not commit, Gang Greene sets out to expose the students responsible, who are trying to blackmail Jackson into helping them cheat on an important test.